2013
DOI: 10.1200/jco.2012.48.1432
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial to Assess the Impact of Venlafaxine and Soy Protein on Hot Flashes and Quality of Life in Men With Prostate Cancer

Abstract: A B S T R A C T PurposeHot flashes occur in approximately 80% of androgen-deprived men. Few intervention studies have been conducted to relieve hot flashes in men. Patients and MethodsEligible androgen-deprived men were randomly assigned to one of four daily regimens (2 ϫ 2 factorial design) for 12 weeks: milk protein powder and placebo pill, venlafaxine and milk protein powder, soy protein powder and placebo pill, or venlafaxine and soy protein powder. The primary end point was hot flash symptom severity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…Two dietary RCTs of 99 participants investigated the efficacy of 12 weeks of soy supplementation on QoL, androgen deprivation symptoms or metabolic risk factors in men with PCa (Sharma et al 2009, Napora et al 2011, Vitolins et al 2013. One study had four treatment groups randomising venlafaxine and venlafaxine placebo as well as soy and soy placebo (Vitolins et al 2013).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two dietary RCTs of 99 participants investigated the efficacy of 12 weeks of soy supplementation on QoL, androgen deprivation symptoms or metabolic risk factors in men with PCa (Sharma et al 2009, Napora et al 2011, Vitolins et al 2013. One study had four treatment groups randomising venlafaxine and venlafaxine placebo as well as soy and soy placebo (Vitolins et al 2013).…”
Section: Interventionsmentioning
confidence: 99%
“…One study had four treatment groups randomising venlafaxine and venlafaxine placebo as well as soy and soy placebo (Vitolins et al 2013). For this review, we only included the treatment groups where venlafaxine placebos were used so as to compare the effects of soy supplementation.…”
Section: Interventionsmentioning
confidence: 99%
“…These data should be regarded as preliminary only, given the small sample (n=36). Some support for soy supplementation in the diet of men on ADT has been reported by Vitolins and colleagues [53] in a trial evaluating soy protein supplementation (20 g with 160 mg isoflavones, n = 30), versus Venlafaxine (75mg once daily, n =30), versus combined soy and Venlafaxine (n =30) or milk powder placebo (n =30). The authors reported a significant and clinically relevant difference in FACT-P after 12 weeks in men taking soy protein (mean = 113 points, SE = 6 points) versus men who did not take soy protein (mean = 104 points, SE = 6 points).…”
Section: Dietmentioning
confidence: 99%
“…sachet of powder [soy isoflavones or placebo] and single tablet [venlafaxine or placebo]) had a compliance rate of 92% [366] . While this trial aimed to ameliorate ADT-induced hot flushes, the high compliance observed supports our findings that a powder sachet and single tablet appears to be a feasible approach for administering a multi-nutrient supplement in these men.…”
Section: Attrition and Adherencementioning
confidence: 99%